2012
DOI: 10.1371/journal.pone.0051777
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved Dental Pulp Tissues of Exfoliated Deciduous Teeth Is a Feasible Stem Cell Resource for Regenerative Medicine

Abstract: Human exfoliated deciduous teeth have been considered to be a promising source for regenerative therapy because they contain unique postnatal stem cells from human exfoliated deciduous teeth (SHED) with self-renewal capacity, multipotency and immunomodulatory function. However preservation technique of deciduous teeth has not been developed. This study aimed to evaluate that cryopreserved dental pulp tissues of human exfoliated deciduous teeth is a retrievable and practical SHED source for cell-based therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
139
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 52 publications
0
139
0
7
Order By: Relevance
“…The hSHEDS are being widely investigated for their differentiation ability to odontoblastic cells, osteoblasts, endothelial cells, neural cells, adipocyte cells, and myocyte cells for tissue engineering purposes, in conditions which include, muscular dystrophy, spinal cord injuries, and various skeletal defects (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The hSHEDS are being widely investigated for their differentiation ability to odontoblastic cells, osteoblasts, endothelial cells, neural cells, adipocyte cells, and myocyte cells for tissue engineering purposes, in conditions which include, muscular dystrophy, spinal cord injuries, and various skeletal defects (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Exfoliated deciduous teeth are usually discarded as medical waste; therefore, SHED can be easily collected from exfoliated deciduous teeth with cooperation and agreement from the patient. SHED express embryonic stem cell markers Oct-4 and Nanog, the mesenchymal stem cell marker stromal precursor antigen-1 (STRO-1), and the neuronal stem cell marker Nestin and possess high prolifer-ation capacity; SHED also show multidifferentiation potential and can differentiate into neuronal, osteogenic, adipogenic, and hepatogenic cells (Ma et al, 2012;Miura et al, 2003;Yamaza et al, 2015). SHED have been shown to be able to differentiate into neurons, astrocytes, and oligodendrocytes (Jarmalavičiūtė et al, 2013;Miura et al, 2003;Nourbakhsh et al, 2011;Sakai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies to test cryopreserving SHED have shown that these cells can recover after thawing and behave similarly to the non-cryopreserved counterparts [14]. When the deciduous…”
mentioning
confidence: 99%